Review of ‘Audubon’s Birds of America’ at the National Museum of Scotland - Peter Adkins (19, 2022)
This is a review of the exhibition ‘Audubon’s Birds of America’, held at the National Museum of Scotland, Edinburgh from 12 February to 8 May 2022.